A comparative study of open and closed heat-engines for small-scale CHP applications - Eames, Ian W.; Evans, Kieran; Pickering, Stephen (MDPI, 2016)
In this paper the authors compare and contrast open and closed-cycle heat engines. First of all, by way of example and to aid discussion, the performance of proprietary externally heated closed-cycle Stirling engines is compared with that of internally heated open Otto cycle engines. Both types of engine have disadvantages and merits and this suggested that in order to accommodate the best of both engine types an externally-heated open-cycle engine might offer a more satisfactory solution for small-scale combined heat and power (CHP) systems. To investigate this possibility further the paper goes on to compare the performance of externally-heated and recuperated Joule hot-air cycle engines with that of an externally-heated closed Stirling cycle engines. The results show that an externally heated recuperated open Joule cycle engine can exceed that of a closed cycle Stirling engine operating between the same heat source and sink temperatures when a variable temperature heat source is used.